Fostering Intrapreneurial Intention Through Intrapreneurial Orientation in HEIs Of Pakistan: Investigating Mediating Role of Entrepreneurial Skills and Psychological Empowerment - Khan, Muhammad Rahies; Askari, Mahrukh; Laila, anita; Ali, Qamber (UW Journal of Management Sciences, 2024)
Background: The dynamic organizational environment has greatly changed traditional commercial and organizational operations across sectors. However, there hasn't been much analysis of how employees fit into this unstable environment. Purpose: This study intends to evaluate how people's entrepreneurial orientation affects their intrapreneurial intention within Pakistan's higher education institutions (HEIs). The study also looks at how entrepreneurial ability and psychological empowerment act as mediators. Methodology: A total of 230 authentic questionnaires from HEIs in Karachi, Pakistan, were used to collect data using cluster sampling strategies. Smart PLS was used to analyse the collected data and evaluate the structural model. While considering the mediating functions of psychological empowerment and entrepreneurial skill, the study investigates the relationship between individual intrapreneurial intention and entrepreneurial attitude (especially risk, inventiveness, and proactivity). Findings: The results show that the association between personal entrepreneurial orientation and intrapreneurial intention is partially mediated by both entrepreneurial skills and psychological empowerment, with a strong direct influence seen before mediation. Furthermore, it was discovered that entrepreneurial competence somewhat mediates risk and innovativeness, whereas psychological empowerment mediates proactivity but not the other components. Implications: According to the study, developing people's abilities in HEI contexts can help them be more innovative and take more risks. Additionally, encouraging psychological independence and empowerment might boost people's initiative. Originality: The intrapreneurial intention among HEIs is a new concept and through this paper, we have empirically tested the hypothesized relationships of proposed variables in the Pakistani context which is rarely been discussed. Keywords: Intention, Psychological Empowerment, Entrepreneurial Skills, HEIs